Elevated Levels of Urinary Podocyte-Derived Microparticles in Nephrotic Syndrome - Eka Laksmi Hidayati; Bambang Supriyatno; Sudung Oloan Pardede; Partini Pudjiastuti Trihono; Dewi Sukmawati; Dewi Wulandari; Oke Rina Ramayani (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Nephrotic syndrome (NS) is the most common glomerular disease in childhood. The proposed hypothesis for the pathogenesis of this disease has changed over time, from immune dysregulation theory and systemic circulating factors theory, to the growing recognition of podocytopathies’ role. The existance of podocytopathies is usually examined by using podocyte-derived microparticles (MPs), such as nephrin, podocin, and podocalyxin (PCX). Therefore in this study, the difference between nephrin, podocin, and PCX expressions in NS children and healthy children was investigated.METHODS: An observational cross-sectional study was conducted, involving 33 children with NS and 22 age-matched healthy children as controls. Urine samples were collected from each subject in the early morning, before being processed and incubated with antibodies to detect nephrin, podocin, and PCX. The processed samples were then analyzed with flow cytometer methods.RESULTS: NS subjects had significantly higher expression of all three urinary podocyte-derived MPs compared to the control subjetcs. Nephrin, podocin, and PCX showed good discrimination in NS subjects with the area under curve (AUC) of 0.895, 0.849, and 0.728, respectively.CONCLUSION: This study revealed the differential expression of podocyte proteins in NS subjects compared to healthy controls. This supports the role of podocytopathies in the pathogenesis of NS. Therefore, nephrin, podocin, and PCX might have potentials to be future non-invasive diagnostic tools in glomerular disease.KEYWORDS: nephrin, nephrotic syndrome, podocalyxin, podocin, podocyte, urinary microparticle